Didactic Innovative and Communicative Activities for Language Teachers - Chávez, Jessica; Murga, Norma (CIEX JOURNAL, 2017)
Didactic activities contribute to promote students’ competences, assisting them to develop their abilities. This research presents a proposal of didactic innovative and communicative activities for language teachers when applying CIEX methodology to motivate students. The main contribution of this research is a proposal for implementing language-teaching activities to enhance pupil’s language learning process by developing their communicative competence. The considerations of language teachers are vital for this proposal. Therefore, this research has gathered information from students and teachers using both: qualitative and quantitative techniques.